Regulation of central and regional governments in managing foodservice with environmental insight in/ Zaitun Djamal ... [et al.] - Zaitun, Djamal; Siagian, Albiner; Julianti, Elisa; Setianingsih, Rita M. (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Policies established by the government bring many positive impacts on foodservice providers, from the occurrence of food poisoning and environmental pollution. However, not all policies are followed by the business providers and tend to be ignored. Therefore, the purpose of this study is to determine which central and local government regulations are implemented by the foodservice business management, at Medan city. The research method is carried out qualitatively. The findings show that there are still violations and irregularities committed by foodservice businesses in various government regulations. Thus, tighter supervision from related parties required for this regulation to run.